Diagnosis and Treatment of Gastroesophageal Reflux Disease in Infants and Children - Yvan Vandenplas (Canadian Journal of Gastroenterology)
Gastroesophageal reflux is a frequent, nonspecific phenomenon in infants and children. The recommended approach for infants with uncomplicated regurgitation is the reassurance of the parents about the physiological nature of excessive regurgitation, and if necessary, completed with dietary recommendations for formula-fed infants. If, despite these efforts, the symptoms persist, the administration of prokinetics such as cisapride is recommended before investigations such as esophageal pH monitoring are begun. Cisapride is the drug of choice because it has the best efficacy and safety profile. In infants and children presenting with symptoms that suggest esophagitis, endoscopy of the upper gastrointestinal tract is recommended. If there is severe esophagitis, acid suppression with H2 receptor antagonists or proton pomp inhibitors is recommended, eventually in combination with prokinetics. In life-threatening situations, or in patients who are resistant to or dependent on acid suppressive medication, a surgical procedure such as laparoscopic Nissen should be considered.